2006
DOI: 10.1159/000097816
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deficiency and Endothelial Dysfunction in Men with End-Stage Kidney Disease Receiving Maintenance Hemodialysis

Abstract: Objectives and Methods: Two thirds of men with end-stage kidney disease (ESKD) have serum testosterone levels in the hypogonadal range. We examined if low serum testoster- one levels were correlated with measures of endothelial dysfunction in ESKD. Bilateral common carotid artery (CCA) intima-media thickness (IMT) and atherosclerotic plaque occurrence, left ventricular mass index, flow- (FMD) and nitrate-mediated vasodilatation (NMD) of the brachial artery were determined by ultrasound imaging in 100 nondiabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 89 publications
1
37
0
1
Order By: Relevance
“…Testosterone deficiency may have impact on endothelial dysfunction and therewith being an etiological factor in ED. 25 To elucidate the molecular mechanisms of hypogonadism in men with ESRD, Dunkel et al 26 tested the capacity of serum from ESRD patients to inhibit recombinant human LH receptor activity. Using a cell line expressing functional human LH receptors, they found that adenosine 3 0 5 0 -monophosphate production was markedly inhibited by sera from the patients, compared to sera from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testosterone deficiency may have impact on endothelial dysfunction and therewith being an etiological factor in ED. 25 To elucidate the molecular mechanisms of hypogonadism in men with ESRD, Dunkel et al 26 tested the capacity of serum from ESRD patients to inhibit recombinant human LH receptor activity. Using a cell line expressing functional human LH receptors, they found that adenosine 3 0 5 0 -monophosphate production was markedly inhibited by sera from the patients, compared to sera from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The score for each item ranges from 0 to 5 for questions 1-10, 0 meaning no sexual activity/no attempt to have sexual intercourse, and from 1 to 5 for questions [11][12][13][14][15]. The severity of ED was classified using five categories: no ED (EF score: 26-30), mild (EF score: [22][23][24][25], mild to moderate (EF score: 17-21), moderate (EF score: 11-16) and severe (EF score: 6-10). 15 At baseline complete blood count, serum creatinine, albumin, PSA, alanine aminotransferase and serum hormone levels including follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), total and free T, sex hormone binding globulin (SHBG) and intact parathyroid hormone were measured.…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been reported that low endogenous testosterone values were also associated with increased risk of death in male hemodialysis patients (7,8). Interestingly, testosterone deficiency in men undergoing hemodialysis has also been related to arterial thickening, atherosclerotic plaque occurrence, and reduced flowmediated dilation (FMD) (9). The high prevalence and amenability to intervention makes hypogonadism an attractive potential therapeutic target in CKD men, meriting further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In a small study that included male HD patients without diabetes, low testosterone levels were associated with endothelial dysfunction and atherosclerosis (15). Interestingly, Carrero et al (16) recently demonstrated in a Swedish HD cohort that low serum testosterone levels were significant predictors of mortality, irrespective of age and inflammation, but this was abolished after correction for serum creatinine, used there as a surrogate of muscle mass (16).…”
mentioning
confidence: 99%